Conflict and cooperation over sex: the consequences of social and genetic polyandry for reproductive success in dunnocks. (1st October 2015) - Santos, Eduardo S. A.; Santos, Luana L. S.; Lagisz, Malgorzata; Nakagawa, Shinichi; Sheldon, Ben
Summary Conflict and cooperation within and between the sexes are among the driving forces that lead to the evolution of mating systems. Among mating strategies, female genetic polyandry and male reproductive cooperation pose challenging evolutionary questions regarding the maintenance of systems where one sex suffers from reduced fitness. Here, we investigate the consequences of social and genetic polyandry for reproductive success of females and males in a population of the dunnock, Prunella modularis. We show that female multiple mating ameliorates the negative effects of inbreeding. We, however, found little evidence that females engage in extra‐group (pair) mating with less related or more heterozygous males. Breeding in socially polyandrous groups reduced the amount of paternity lost to extra‐group males, such that, on average, cobreeding and monogamous males fledged a similar number of young. Importantly, c. 30% of cobreeding male dyads were related, suggesting they could gain indirect fitness benefits. Taken together, cobreeding males achieve equivalent reproductive success to monogamous counterparts under most circumstances. Our study has revealed unexpected complexities in the variable mating system of dunnocks in New Zealand. Our results differ from the well‐known Cambridge dunnock study and can help our understanding of the evolution and maintenance of various breeding systems in the animal kingdom.